2018
DOI: 10.1111/1365-2656.12786
|View full text |Cite
|
Sign up to set email alerts
|

Disease implications of animal social network structure: A synthesis across social systems

Abstract: The disease costs of sociality have largely been understood through the link between group size and transmission. However, infectious disease spread is driven primarily by the social organization of interactions in a group and not its size. We used statistical models to review the social network organization of 47 species, including mammals, birds, reptiles, fish and insects by categorizing each species into one of three social systems, relatively solitary, gregarious and socially hierarchical. Additionally, u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
137
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(149 citation statements)
references
References 78 publications
(120 reference statements)
4
137
0
Order By: Relevance
“…Our disease simulations showed that the spatial structure of empirically derived badger contact networks reduced the probability of large epidemics. This provides evidence for the importance of a "social bottleneck" (Nunn, Craft, et al, 2015;Sah et al, 2018;VanderWaal et al, 2014;White et al, 2017) in disease transmission functioning at a population level. We also found considerable variation between individuals in the size of epidemics they generated in networks with realistic spatial and social group structure that varied according to both their local (direct connections) and global position (role in broader network connectivity) F I G U R E 5 (a) The proportion of variation in (a) the number of secondary infections and (b) epidemic size explained by the choice of the initially infected individual in the three network types for each transmission probability used in the study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Our disease simulations showed that the spatial structure of empirically derived badger contact networks reduced the probability of large epidemics. This provides evidence for the importance of a "social bottleneck" (Nunn, Craft, et al, 2015;Sah et al, 2018;VanderWaal et al, 2014;White et al, 2017) in disease transmission functioning at a population level. We also found considerable variation between individuals in the size of epidemics they generated in networks with realistic spatial and social group structure that varied according to both their local (direct connections) and global position (role in broader network connectivity) F I G U R E 5 (a) The proportion of variation in (a) the number of secondary infections and (b) epidemic size explained by the choice of the initially infected individual in the three network types for each transmission probability used in the study.…”
Section: Discussionmentioning
confidence: 85%
“…However, recent advances in bio-logging technology to collect high-resolution social contact data, and methods of network analysis, have enabled the quantification of social interactions among wild animals (Blyton, Banks, Peakall, Lindenmayer, & Gordon, 2014;Hamede, Bashford, McCallum, & Jones, 2009;Hirsch, Reynolds, Gehrt, & Craft, 2016;Pinter-Wollman et al, 2013;White et al, 2017). This has facilitated modeling work that has provided many important insights into how social systems and network structure influences the transmission of directly transmitted infections in nonhuman animals (e.g., Sah et al, 2018). However, an important gap remains in understanding the role of stable social group structure at a population level (cf.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, there is thus an opportunity to carry out comparative network studies across multiple species to identify general patterns and generate broad principles [19]. However, such studies are currently challenging due to differences in data collection methods, a lack of standardized formats for published data, and the absence of a centralized data repository [20]. While such repositories exist for human interaction data [2,3,16,1], there is a gap for social network datasets across multiple taxonomic groups.…”
Section: Background and Summarymentioning
confidence: 99%
“…Weinstein's (2018) Review of a computer vision for animal ecology (Weinstein 2018). Sah's (2018) Review on disease implications of animal social network structure (Sah, Mann, & Bansal, 2018).…”
Section: S Hortlis Ted Paper Smentioning
confidence: 99%